The Relevance of Modern Scientific Research in Pedagogy: Ukrainian-Polish Discourse - Khoruzha, Liudmyla (Educological discourse, 2024)
The article provides a comparative analysis of the scientific investigations of Polish and Ukrainian scientists regarding the subject matter and content of modern pedagogical research. New challenges, the world crisis, a full-scale war in Ukraine - in one way or another influence the choice of research topics, determine their timeliness and expediency. It is noted that a wide interdisciplinary pedagogical approach to solving educational problems is clearly observed in Polish research. According to the thematic direction, scientific investigations have an applied nature, meet the demands of science and society. At the same time, the subject matter of scientific issues of domestic pedagogical research is mainly local in nature and does not fully correlate with modern social demands. It was concluded that it is needed to develop methodological foundations of pedagogy in conditions of instability and transgressivity. A list of pedagogical topics that are relevant for study in these conditions is presented.